Recent Advances in Heavy Metals Induced Effect on Male Reproductive Function-A Retrospective - A.Roy Chowdhury (Al Ameen Medical College, 2009)
Reproductive hazards from metal exposure in males are one of the fastest growing areas of concern in toxicology today. Exposure to different heavy metals causes irreversible toxic insult to male reproductive system. Heavy metals produce cellular impairments at structural and functional level in male reproductive system. The effect of heavy metals, such as lead, mercury, cadmium, chromium and arsenic on male reproduction has been studied in details in various experimental species. But data on humans are steadily building up. Metals could interfere with the gametogenic cells or Leydig cell or spermatozoa directly in semen. These effects may results in reduced fertility or associated with pregnancy wastage, congenital malformation associated with genetic diseases. Moreover, the features of heat stress protein (hsp), Androgen-Binding Protein (ABP), Cadherin and many other stressor protein along with reactive oxygen species (ROS) and neuro-endocrine mechanism are highly affected by these heavy metals exposure. Still the data are inadequate and need confirmation.